2020
DOI: 10.15388/infedu.2020.11
|View full text |Cite
|
Sign up to set email alerts
|

Scratch-Based User-Friendly Requirements Definition for Formal Verification of Control Systems

Abstract: Control systems are becoming ever more commonly used in everyday life. This is true both in industry and in the domestic domain, in the form of e.g., smart home systems. The quality of such systems can be increased by using formal verification methods, such as the model checking technique, to make sure that the designed system fulfills all user requirements. The requirements are usually written as temporal logic formulas. However, the technical skills of future users or the mathematical background knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The only thing the designer has to do is to describe a net (or a subnet) in text form (the verifiable model is then generated) and to prepare the list of requirements. These are usually delivered in the form of the temporal logic formulas, but it is also possible (when needed, e.g., in the case of a user-centred design where the customer is involved in the development process) to simplify the requirement definition process by using the alternate forms, such as a user-friendly Scratch-based definition [ 71 ].…”
Section: Case Study Example Of the Proposed Methodsmentioning
confidence: 99%
“…The only thing the designer has to do is to describe a net (or a subnet) in text form (the verifiable model is then generated) and to prepare the list of requirements. These are usually delivered in the form of the temporal logic formulas, but it is also possible (when needed, e.g., in the case of a user-centred design where the customer is involved in the development process) to simplify the requirement definition process by using the alternate forms, such as a user-friendly Scratch-based definition [ 71 ].…”
Section: Case Study Example Of the Proposed Methodsmentioning
confidence: 99%
“…Mainly due to their graphical modeling approach, which makes them flexible and more human-oriented than, for example, text-based or mathematical-based notation techniques, semi-formal (visual) methods have been very popular [1][2][3]. Most of them allow for the modeling of various system view points at different abstraction levels including, for instance, models specifying user requirements, system and architectural design.…”
Section: Introductionmentioning
confidence: 99%
“…There are some approaches that may enrich the learning process, mainly by using some dedicated tools or other user-friendly forms, like interactive games or applications. In our previous paper, we proposed a Scratch-based method of requirements definition for control systems verification (Grobelna, 2020). That study showed that when using Scratchit is easier for the students to define the requirements, in comparison to conventional temporal logic formulas.…”
Section: Introductionmentioning
confidence: 99%